Long-term safety and tolerability of aripiprazole lauroxil in patients with schizophrenia. (15th August 2018) - Nasrallah, Henry A.; Aquila, Ralph; Du, Yangchun; Stanford, Arielle D.; Claxton, Amy; Weiden, Peter J.
Abstract : Objective: Safety and tolerability of long-term treatment with the long-acting antipsychotic aripiprazole lauroxil (AL) were evaluated in patients with schizophrenia. Methods: This was an international, multicenter, phase 3, 52-week safety study of 2 fixed doses of AL (441 mg or 882 mg intramuscular every 4 weeks). Safety endpoints included adverse events (AEs) and extrapyramidal symptoms (EPS) including akathisia, injection-site reactions (ISRs), and clinically relevant changes in metabolic and endocrine values. Results: Of 478 patients entering this study, 236 (49%) continued from a previous 12-week, phase 3 efficacy study of AL, and 242 (51%) were newly enrolled. Overall, 77% and 23% of patients received AL 882 mg (N = 368) and 441 mg (N = 110), respectively. AEs occurred in 50.4% of patients; most were mild (28.7%) or moderate (18.2%). The most common AEs were insomnia (8.4%) and increased weight (5.0%). Akathisia was reported as an AE in 3.8% of the overall population, with higher rates in patients initiating AL on study entry than those continuing on AL. EPS-related AEs occurred in 9.4% of patients, and AEs related to metabolic parameters were reported in 4.6% of patients. Weight gain was minimal (0.8 kg), and no clinically relevant changes were observed for metabolic parameters. The overall incidence of ISRs was 3.8%; most were associated with the initial injections in patients receiving their first injection in this study. Conclusion: Long-term treatment with AL is generally well tolerated, with a safety profile consistent with that of oral aripiprazole. It is a suitable option for patients with schizophrenia.